Comparative analysis of top cryptocurrencies to other financial markets - Ilagan, Chadwick Wayne G. (Animo Repository, 2022)
Investing in oneself, a service, a business, and others, has been practiced for ages. Cryptocurrency has gained attention recently. In order to determine if cryptocurrencies are a good investment compared to other established financial markets like the US Stock Market, Philippine Stock Market, and Commodity Futures Market, the researchers used this information to further their research. This study aims to statistically examine whether there are any differences in the mean monthly returns of cryptocurrencies compared to other financial markets and to see whether there is any market link. The degree of market volatility was examined in this study. Because the researchers found promise in cryptocurrencies, this study tried to thoroughly conclude if the returns of cryptocurrencies are statistically significant compared to the other financial markets. Using panel regression, the researchers thoroughly examined the association between six cryptocurrencies and four other financial markets. Bitcoin, Digital Cash, Dogecoin, Ethereum, Litecoin, and Ripple exhibit little to no link with other conventional financial markets after using the approach and examining the data. It is in line with research by Chuen et al. (2018) and Klabbers (2017), who found that cryptocurrencies have a very poor association with conventional asset classes. Although the study's findings showed no statistically significant difference between the mean monthly returns of cryptocurrencies and those of other financial markets, it is nevertheless important to note. To examine the entire breadth of the possibilities of cryptocurrencies, it is advised to apply other techniques. The volatility of cryptocurrencies is also typically higher than that of conventional financial markets.